Characterization of P. falciparum dipeptidyl aminopeptidase 3 specificity identifies differences in amino acid preferences between peptide‐based substrates and covalent inhibitors. (24th June 2019) - de Vries, Laura E.; Sanchez, Mateo I.; Groborz, Katarzyna; Kuppens, Laurie; Poreba, Marcin; Lehmann, Christine; Nevins, Neysa; Withers‐Martinez, Chrislaine; Hirst, David J.; Yuan, Fang; Arastu‐Kapur, Shirin; Horn, Martin; et al.
Abstract : Malarial dipeptidyl aminopeptidases (DPAPs) are cysteine proteases important for parasite development thus making them attractive drug targets. In order to develop inhibitors specific to the parasite enzymes, it is necessary to map the determinants of substrate specificity of the parasite enzymes and its mammalian homologue cathepsin C (CatC). Here, we screened peptide‐based libraries of substrates and covalent inhibitors to characterize the differences in specificity between parasite DPAPs and CatC, and used this information to develop highly selective DPAP1 and DPAP3 inhibitors. Interestingly, while the primary amino acid specificity of a protease is often used to develop potent inhibitors, we show that equally potent and highly specific inhibitors can be developed based on the sequences of nonoptimal peptide substrates. Finally, our homology modelling and docking studies provide potential structural explanations of the differences in specificity between DPAP1, DPAP3, and CatC, and between substrates and inhibitors in the case of DPAP3. Overall, this study illustrates that focusing the development of protease inhibitors solely on substrate specificity might overlook important structural features that can be exploited to develop highly potent and selective compounds. Abstract : We have used peptide‐based libraries of substrates and covalent inhibitors to characterize the specificity of Plasmodium dipeptidyl aminopeptidase 3, a protease important for red blood cell invasion. Interestingly, we observed significant differences in amino acid preference between substrates and inhibitors, and showed that highly potent and specific inhibitors can be developed based on the sequences of nonoptimal peptide substrates.